Photovoltaic cable

By using a high-polymer polyvinyl chloride resin and specific additives in the insulation layer design, combined with a steel-plastic composite waterproof layer and a tin-plated copper/aluminum alloy conductor structure, the heat resistance and flame retardancy issues of photovoltaic cables are solved, achieving material recyclability and cost reduction, while meeting high-temperature flame retardancy requirements.

CN121108648APending Publication Date: 2025-12-12TBEA XINJIANG CABLE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511219255.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing photovoltaic cables have poor heat resistance and flame retardancy, which makes it easy for flames to spread along the cable in the event of a fire. In addition, the cost of radiation cross-linking equipment is high and the materials cannot be recycled.

Method used

The insulation layer matrix is ​​made of polyvinyl chloride resin with a degree of polymerization of 2500, combined with specific heat-resistant plasticizers, flame retardants, heat stabilizers and other components to form an insulation layer that does not require radiation cross-linking. A steel-plastic composite waterproof layer is set on the outside of the insulation layer. The conductor adopts a stranded structure of tin-plated copper or aluminum alloy, and the sheath layer adopts a specific formula material.

Benefits of technology

It improves the heat resistance and flame retardant properties of photovoltaic cables, enables the materials to be repeatedly recycled, reduces production costs, and meets the requirements for long-term use at high temperatures and flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121108648A_ABST
    Figure CN121108648A_ABST
Patent Text Reader

Abstract

The invention discloses a photovoltaic cable, and relates to the technical field of cables, and the photovoltaic cable comprises an insulating layer. The insulating layer comprises the following components in percentage by mass: 45%-48% of polyvinyl chloride resin with the polymerization degree of 2500, 20%-24% of a heat-resistant plasticizer, 5.7%-7% of a heat stabilizer, 1.13%-1.18% of an antioxidant, 12%-15.5% of a flame retardant, 6%-7.5% of a filler, 2.25%-2.4% of a processing aid, 0.5%-1.5% of a lubricant and 0.02% of a coloring agent; wherein the heat-resistant plasticizer is prepared from trioctyl trimellitate, tridecyl trimellitate and epoxidized soybean oil; or the heat-resistant plasticizer comprises trioctyl trimellitate and tridecyl trimellitate. The specific heat-resistant plasticizer, the flame retardant, the heat stabilizer, the antioxidant, the filler, the processing aid, the lubricant and the coloring agent are introduced according to a certain mass ratio on the basis of the high-polymerization-degree polyvinyl chloride, so that the photovoltaic cable has good heat resistance and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cable technology, and more particularly to photovoltaic cables. Background Technology

[0002] Currently, commonly used photovoltaic cable products typically undergo electron accelerator irradiation crosslinking after the extrusion of irradiated crosslinked halogen-free low-smoke flame-retardant polyolefin insulation material and irradiated crosslinked halogen-free low-smoke flame-retardant polyolefin sheath material. This process alters the molecular structure of the polyolefin, thereby improving the temperature resistance of the photovoltaic cable products.

[0003] However, the large footprint and high cost of electron accelerator irradiation equipment significantly increase the cost of photovoltaic cable products. Furthermore, the insulation and sheathing materials after irradiation cross-linking cannot be recycled. In addition, this photovoltaic cable product has poor flame retardant properties, making it easier for flames to spread along the cable in the event of an accidental fire, potentially causing greater damage to the photovoltaic power station. Summary of the Invention

[0004] The main purpose of this application is to provide photovoltaic cables that address the technical problems of poor heat resistance and flame retardancy in existing photovoltaic cables.

[0005] To achieve the above objectives, this application proposes a photovoltaic cable including an insulation layer;

[0006] The insulation layer comprises the following components by weight percentage: 45%–48% polyvinyl chloride resin with a degree of polymerization of 2500, 20%–24% heat-resistant plasticizer, 5.7%–7% heat stabilizer, 1.13%–1.18% antioxidant, 12%–15.5% flame retardant, 6%–7.5% filler, 2.25%–2.4% processing aid, 0.5%–1.5% lubricant, and 0.02% colorant;

[0007] The heat-resistant plasticizers include trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil; or, the heat-resistant plasticizers include trioctyl trimellitate and tridecyl trimellitate.

[0008] In one embodiment, the mass ratio of trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil is (4.50–9.48):(11.85–16.28):(0–1.90).

[0009] In one embodiment, the flame retardant comprises a primary flame retardant, a secondary flame retardant, and a synergist in a mass ratio of (2.33–3.79):(2.33–3.79):(4.74–9.30);

[0010] The primary flame retardant is antimony trioxide, the secondary flame retardants are aluminum hydroxide and magnesium hydroxide in a mass ratio of 2:1, and the synergist is zinc borate or zinc aluminate.

[0011] In one embodiment, the heat stabilizer is an organic calcium-zinc composite environmentally friendly stabilizer, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], the filler is combusted kaolin, the processing aid is an acrylate copolymer, the lubricant is light barium stearate, and the colorant is Lisol Ruby Red.

[0012] In one embodiment, the polyvinyl chloride resin with a degree of polymerization of 2500 accounts for 46.50% by mass, trioctyl trimellitate accounts for 4.65% by mass, tridecyl trimellitate accounts for 16.28% by mass, heat stabilizer accounts for 6.98% by mass, antioxidant accounts for 1.16% by mass, flame retardant accounts for 13.93% by mass, filler accounts for 6.98% by mass, processing aid accounts for 2.23% by mass, lubricant accounts for 1.16% by mass, and colorant accounts for 0.02% by mass.

[0013] In one embodiment, the photovoltaic cable further includes a waterproof layer disposed outside the insulation layer;

[0014] The waterproof layer is made of steel-plastic composite tape tightly wrapped longitudinally. The steel-plastic composite tape includes a steel layer and a plastic layer. The steel layer is placed outside the insulation layer, and the plastic layer is placed outside the steel layer.

[0015] In one embodiment, the photovoltaic cable further includes a conductor disposed inside the insulation layer, the conductor being a tin-plated copper conductor or a type II aluminum alloy conductor.

[0016] In one embodiment, the tin-plated copper conductor is formed by twisting together multiple coarse tin-plated copper wires in a regular arrangement and in layers. The outer diameter of the coarse tin-plated copper wires is 0.4 mm to 0.64 mm, and the outer diameter of the tin-plated copper conductor is 2.00 mm to 8.53 mm.

[0017] In one embodiment, the outer diameter of the second type of aluminum alloy conductor is 2.04 mm to 7.47 mm, and the diameter of a single wire is 0.68 mm to 2.49 mm.

[0018] In one embodiment, the photovoltaic cable further includes a sheath layer disposed on the outermost side of the photovoltaic cable.

[0019] One or more technical solutions proposed in this application have at least the following technical effects:

[0020] The insulation layer provided in this application uses polyvinyl chloride resin with a degree of polymerization of 2500 as the insulation layer matrix. This not only improves the heat resistance of the photovoltaic cable, but also eliminates the need for electron irradiation crosslinking as required by polyolefin insulation materials. Therefore, the insulation layer provided in this application has the advantages of being recyclable and having low production costs. Furthermore, this application introduces a certain mass ratio of specific heat-resistant plasticizers, flame retardants, heat stabilizers, antioxidants, fillers, processing aids, lubricants, and colorants into the high-polymerization-degree polyvinyl chloride to improve the insulation matrix. This significantly improves the temperature resistance, flame retardancy, processing performance, and electrical properties of the insulation layer material. Trioctyl trimellitate and tridecyl trimellitate are used to raise the heat resistance of the insulation layer to 125°C. Epoxidized soybean oil is used to stabilize the heat resistance environment of trioctyl trimellitate and tridecyl trimellitate. The flame retardant is used to improve the flame retardancy of the insulation layer, thereby obtaining a photovoltaic cable that can be used for a long time at a temperature of 125°C and has good flame retardant performance. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the cross-sectional structure of the photovoltaic cable provided in this application.

[0023] Explanation of icon numbers:

[0024] 1. Insulation layer 1; 2. Waterproof layer; 3. Conductor; 4. Sheath layer.

[0025] The purpose, features, and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0026] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0027] It should be noted that if the embodiments of this application involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.

[0028] Furthermore, if the embodiments of this application involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution that simultaneously satisfies A and B. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed in this application.

[0029] In this application, when numerical intervals (i.e., numerical ranges) are involved, unless otherwise specified, the distribution of selectable numerical values ​​within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.

[0030] Figure 1 This is a schematic diagram of the cross-sectional structure of a photovoltaic cable provided in this application. This application proposes a photovoltaic cable, as shown in the reference... Figure 1The photovoltaic cable includes an insulation layer 1. The insulation layer 1 comprises the following components by weight percentage: 45%–48% polyvinyl chloride resin with a degree of polymerization of 2500, 20%–24% heat-resistant plasticizer, 5.7%–7% heat stabilizer, 1.13%–1.18% antioxidant, 12%–15.5% flame retardant, 6%–7.5% filler, 2.25%–2.4% processing aid, 0.5%–1.5% lubricant, and 0.02% colorant; wherein the heat-resistant plasticizer includes trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil; or, the heat-resistant plasticizer includes trioctyl trimellitate and tridecyl trimellitate.

[0031] In related technologies, the insulation and sheath materials used in photovoltaic cables are thermosetting materials, requiring radiation cross-linking, which renders the cross-linked materials unrecyclable. The insulation matrix provided in this embodiment is polyvinyl chloride resin, a thermoplastic material. Therefore, this insulation layer does not require irradiation, and the insulation material can be recycled and reused after the photovoltaic cable has reached its retirement age (e.g., 25 years or more). Thus, the insulation layer provided in this embodiment has the advantages of being recyclable and having low production costs.

[0032] Specifically, in this embodiment, polyvinyl chloride resin with a degree of polymerization of 2500 is used as the insulating layer matrix. Compared with polyvinyl chloride resin with a degree of polymerization of 1000 or 1300, polyvinyl chloride resin with a degree of polymerization of 2500 has better heat resistance, so using it as the insulating layer matrix can improve the heat resistance of the insulating layer to a certain extent.

[0033] Furthermore, this embodiment introduces a specific heat-resistant plasticizer into the high-polymerization-degree polyvinyl chloride (PVC) to improve the heat resistance of the insulation layer to 125°C, thereby enhancing the heat resistance of the photovoltaic cable. This specific heat-resistant plasticizer includes trioctyl trimellitate and tridecyl trimellitate. Tridecyl trimellitate, due to its long-chain alkyl structure and low volatility, exhibits better thermal stability and higher heat resistance than trioctyl trimellitate. Trioctyl trimellitate, with its aromatic ring structure, strong intermolecular forces and low volatility at high temperatures, also demonstrates good thermal stability. Moreover, due to the good compatibility between trioctyl trimellitate and PVC resin, the introduction of trioctyl trimellitate further stabilizes the insulation layer. Therefore, this embodiment effectively improves the heat resistance of the insulation layer through the synergistic effect of trioctyl trimellitate and tridecyl trimellitate. In addition, specific heat-resistant plasticizers include epoxidized soybean oil, which serves only as an auxiliary stabilizer. The epoxy groups in the epoxidized soybean oil can absorb the HCl released from the thermal decomposition of polyvinyl chloride, thus working synergistically with trioctyl trimellitate and tridecyl trimellitate to achieve a stabilizing effect. It should also be noted that in this embodiment, both excessive and insufficient mass proportions of the heat-resistant plasticizer will affect the heat resistance, mechanical and physical properties, and processability of the insulation layer.

[0034] To improve the synergistic effect of the three additives in a specific heat-resistant plasticizer, in one embodiment, the mass ratio of trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil is 4.50–9.48: 11.85–16.28: 0–1.90. It should also be noted that if the mass ratio of trioctyl trimellitate is in the range of 10–20, its excessively high proportion will not only lead to a decrease in the long-term stability of the insulation layer but also reduce its tensile strength, affecting processing performance and causing easy precipitation on the insulation surface, in addition increasing costs. If the mass ratio of tridecyl trimellitate is in the range of 6–10, its excessively low proportion will affect the heat resistance of the material, directly impacting its strength and elongation after heat aging.

[0035] Since the addition of the aforementioned specific heat-resistant plasticizer reduces the flame retardancy of the insulation layer, this embodiment introduces a specific flame retardant based on high-polymerization-degree polyvinyl chloride to improve the flame retardant performance of the insulation layer. In one embodiment, the flame retardant includes a primary flame retardant, a secondary flame retardant, and a synergist in a mass ratio of (2.33–3.79):(2.33–3.79):(4.74–9.30); the primary flame retardant is antimony trioxide, the secondary flame retardant is aluminum hydroxide and magnesium hydroxide in a mass ratio of 2:1, and the synergist is zinc borate or zinc aluminate.

[0036] Specifically, when a photovoltaic cable burns, the antimony trioxide in the insulation layer, upon encountering fire, reacts with the halogens contained in the polyvinyl chloride resin itself through its halogen-antimony synergistic effect to generate volatile antimony halide. The antimony halide can capture the free radicals generated by the chain reaction of the polyvinyl chloride resin during combustion. These free radicals can promote the formation of a char layer in the polyvinyl chloride resin, thereby isolating heat transfer and thus playing a flame-retardant role.

[0037] The secondary flame retardant decomposes upon heating to generate metal oxides and water. The metal oxides absorb heat, thus achieving a flame-retardant effect. Furthermore, since the secondary flame retardant in this embodiment is a compound of two hydroxides, on the one hand, because aluminum hydroxide and magnesium hydroxide have different decomposition temperatures, the photovoltaic cable can decompose into water vapor at different combustion temperatures to remove heat and achieve flame retardancy. The decomposition temperature of aluminum hydroxide is approximately 200°C, while that of magnesium hydroxide is higher at 350°C. On the other hand, aluminum hydroxide is inexpensive, but excessive addition can affect various properties of the insulation material. Although magnesium hydroxide has a smaller impact on the various properties of the insulation material, its cost is higher. Therefore, the compound of the two can balance performance and cost.

[0038] The synergist is a synergistic agent between the primary and secondary flame retardants. Specifically, at a combustion temperature of 250℃~300℃, zinc borate undergoes thermal decomposition and releases water of crystallization. During this process, it absorbs heat, acting as a cooling agent. After cooling, a borosilicate glass layer is formed. This borosilicate glass layer, together with the polyvinyl chloride resin carbon layer, isolates oxygen and heat to achieve flame retardancy. Zinc aluminate decomposes at high temperatures into a ZnAl2O4 spinel structure, forming a dense carbon layer. This dense carbon layer, together with the polyvinyl chloride resin carbon layer, slows down heat penetration to achieve flame retardancy. It should also be noted that if the flame retardant in this embodiment does not include the synergist, i.e., if the flame retardant does not include zinc borate or zinc aluminate, the flame retardant effect will be affected. Specifically, the insulation material will drip during combustion instead of forming a shell that can adhere to the surface of the photovoltaic cable to prevent the inner layer of the photovoltaic cable from burning. This shell refers to the borosilicate glass layer, the dense carbon layer, and the polyvinyl chloride resin carbon layer.

[0039] This application also introduces suitable heat stabilizers, antioxidants, fillers, processing aids, lubricants, and colorants to improve the insulating layer matrix. Based on considerations of material processing performance, cost, and compatibility with polyvinyl chloride resin, in one embodiment, the heat stabilizer is an organic calcium-zinc composite environmentally friendly stabilizer, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], the filler is combustible kaolin, the processing aid is an acrylate copolymer, the lubricant is light barium stearate, and the colorant is Lithol Ruby Red.

[0040] Specifically, the organic calcium-zinc composite environmentally friendly stabilizer, in addition to its environmentally friendly properties, is used to stabilize the thermal degradation of cable materials during processing and use; pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (referred to as antioxidant 1010) is used to stabilize the oxidative degradation of cable materials during processing and use; calcined kaolin is used to improve the electrical properties of cable materials; acrylate copolymers are used to balance the performance of various additives, reducing side effects and improving processing performance while leveraging the advantages of each additive; light barium stearate is used to balance internal and external friction, prevent sticking to equipment, and stabilize the process; and Litholite red is used to distinguish and mark cables.

[0041] Considering temperature resistance, insulation performance, and cost, in one embodiment, the polyvinyl chloride resin with a degree of polymerization of 2500 accounts for 46.50% by mass, trioctyl trimellitate accounts for 4.65% by mass, tridecyl trimellitate accounts for 16.28% by mass, heat stabilizer accounts for 6.98% by mass, antioxidant accounts for 1.16% by mass, flame retardant accounts for 13.93% by mass, filler accounts for 6.98% by mass, processing aid accounts for 2.23% by mass, lubricant accounts for 1.16% by mass, and colorant accounts for 0.02% by mass. Among the flame retardants, antimony trioxide accounts for 2.33% by mass, zinc aluminate accounts for 2.33% by mass, and aluminum hydroxide accounts for 9.30% by mass.

[0042] To better achieve its heat resistance and flame retardant effects, in one embodiment, the thickness of the insulation layer in the photovoltaic cable is 0.7mm to 0.9mm.

[0043] The insulation layer provided in this application uses polyvinyl chloride resin with a degree of polymerization of 2500 as the insulation layer matrix. This not only improves the heat resistance of photovoltaic cables but also eliminates the need for electron irradiation crosslinking as required by polyolefin insulation materials. Therefore, the insulation layer provided in this application has the advantages of being recyclable and having low production costs. Furthermore, this application introduces specific heat-resistant plasticizers, flame retardants, heat stabilizers, antioxidants, fillers, processing aids, lubricants, and colorants in a certain mass ratio to improve the insulation matrix, thereby significantly improving the insulation performance. The insulation material exhibits excellent temperature resistance, flame retardancy, processing performance, and electrical properties. Trioctyl trimellitate and tridecyl trimellitate are used to enhance the heat resistance of the insulation layer to 125°C. Epoxidized soybean oil is used to stabilize the heat resistance of trioctyl trimellitate and tridecyl trimellitate. The flame retardant is used to improve the flame retardancy of the insulation layer. This results in a photovoltaic cable that can be used for a long time at 125°C and has good flame retardancy. This photovoltaic cable is suitable for series cables between photovoltaic modules on the DC side of a photovoltaic power generation system, parallel cables between strings, and parallel cables between strings and DC distribution boxes (combiner boxes).

[0044] Therefore, the performance test results of the insulation layer provided in this embodiment are shown in Table 1 below. As can be seen from Table 1, the insulation layer material provided in this embodiment fully meets the various performance indicators of photovoltaic cable insulation layer. Therefore, the insulation layer material provided in this embodiment can be used as photovoltaic cable insulation layer.

[0045] Table 1 shows the performance of the insulating layer material provided in this embodiment.

[0046]

[0047] In related technologies, irradiated cross-linked halogen-free low-smoke flame-retardant polyolefin insulation materials and irradiated cross-linked halogen-free low-smoke flame-retardant polyolefin sheath materials are halogen-free flame-retardant systems. The materials contain hydrophilic groups, which increases the hygroscopicity of the materials. At the same time, micropores, cracks or interface defects may be formed in the materials during processing, providing channels for moisture penetration. In humid environments, water molecules penetrate the outer sheath through diffusion or capillary action and then penetrate the insulation layer, adsorbing on the insulation surface or in the internal pores, resulting in a decrease in insulation resistance, shortening the cable service life, and increasing maintenance and replacement costs.

[0048] To improve the waterproof performance and further enhance the flame-retardant performance of photovoltaic cables, in one embodiment, the photovoltaic cable also includes a waterproof layer 2. For example... Figure 1 As shown, the waterproof layer 2 is disposed on the outside of the insulation layer 1. The waterproof layer 2 is made of steel-plastic composite tape tightly wrapped longitudinally. The steel-plastic composite tape includes a steel layer and a plastic layer. The steel layer is disposed on the outside of the insulation layer 1, and the plastic layer is disposed on the outside of the steel layer.

[0049] In this embodiment, since steel has a high melting point (reaching over 1500°C), the tightly wrapped steel-plastic composite tape structure can effectively prevent oxygen from entering the cable and seal the insulation layer in this waterproof layer. Even if the insulation layer softens at high temperatures, the molten insulation material will not flow out and thus will not burn, thereby improving the flame retardant performance of the photovoltaic cable.

[0050] In another embodiment, the waterproof layer 2 can also be formed by tightly longitudinally wrapping an aluminum-plastic composite tape. The aluminum-plastic composite tape includes an aluminum layer and a plastic layer, with the aluminum layer disposed outside the insulation layer 1 and the plastic layer disposed outside the aluminum layer. Compared to the tightly longitudinally wrapped aluminum-plastic composite tape structure, the waterproof layer is preferably formed by tightly longitudinally wrapping a steel-plastic composite tape. On the one hand, since the flame temperature is around 850°C, the aluminum-plastic composite tape will melt, thus preventing the waterproof layer from performing its waterproof sealing function and improving the flame-retardant performance of the photovoltaic cable. On the other hand, the strength of the steel-plastic composite is higher than that of the aluminum-plastic composite, so the waterproof layer with the tightly longitudinally wrapped steel-plastic composite tape structure has better water-blocking performance. It should also be noted that since the waterproof layer with the tightly longitudinally wrapped steel-plastic composite tape structure provided in this embodiment has good water-blocking performance, there is no need to set up an additional external water-blocking tape.

[0051] To further ensure the waterproof sealing and flame retardant properties of the waterproof layer, in one embodiment, the joint between the steel layer and the plastic layer after longitudinal wrapping is sealed with hot melt adhesive, or the joint between the aluminum layer and the plastic layer after longitudinal wrapping is sealed with hot melt adhesive.

[0052] Considering cost and performance, in one embodiment, the thickness of the waterproof layer 2 is 0.8mm to 1.1mm; wherein the steel layer or aluminum layer accounts for 70% of the thickness of the waterproof layer 2.

[0053] In this embodiment, a metal composite film is added between the insulation layer and the sheath layer to serve as a waterproof layer. This not only ensures the overall waterproofness of the photovoltaic cable, preventing moisture from reaching the insulation layer and avoiding a decrease in insulation resistance, thus increasing the service life of the photovoltaic cable, but also improves the flame retardant performance of the photovoltaic cable by sealing the insulation layer inside the waterproof layer.

[0054] To improve the production efficiency and reduce the cost of photovoltaic cables, in one embodiment, the photovoltaic cable further includes a conductor 3. For example... Figure 1 As shown, conductor 3 is disposed inside the insulating layer 1, and the conductor is a tin-plated copper conductor or a type II aluminum alloy conductor.

[0055] In one embodiment, the tin-plated copper conductor is formed by twisting together multiple coarse tin-plated copper wires in a regular arrangement and in layers. The outer diameter of the coarse tin-plated copper wires is 0.4 mm to 0.64 mm, and the outer diameter of the tin-plated copper conductor is 2.00 mm to 8.53 mm.

[0056] In related technologies, photovoltaic cable conductors often use Class 5 conductors with small outer diameter of single wires. When the cross-section of Class 5 conductor is small, multiple single wires are usually bundled together into one strand in one go. When the cross-section of Class 5 conductor is large, multiple single wires are first bundled together into one strand, and then the multiple strands are bundled together.

[0057] In this embodiment, the photovoltaic cable conductor is a tin-plated copper conductor, which not only has high safety but is also a specially structured conductor made up of multiple thick tin-plated copper wires twisted together in a regular, layered manner. Therefore, since the tin-plated copper conductor provided in this embodiment does not use a bundling method, the single-wire drawing process and the stranding tools for bundling can be reduced, thereby improving production efficiency and reducing production costs. It should also be noted that since this embodiment does not require high conductor flexibility, the outer diameter of the single wire in this embodiment is relatively large.

[0058] In one example, the outer diameter of a single coarse tin-plated copper wire is 0.4 mm, the outer diameter of the tin-plated copper conductor is 2.00 mm, and the cross-section of the tin-plated copper conductor is 2.5 mm². 2 The tin-plated copper conductor has a structure of 1 / 0.40+6 / 0.40+12 / 0.40 (wires / mm), and its DC resistance at 20℃ is no greater than 7.624Ω / km. In this example, the tin-plated copper conductor is composed of 19 thick tin-plated copper wires with an outer diameter of 0.4mm, arranged in a regular, layered manner and twisted together. The arrangement is as follows: one thick tin-plated copper wire is placed in the center, the second layer of 6 thick tin-plated copper wires are arranged clockwise, and the third layer of 12 thick tin-plated copper wires are arranged clockwise. After the arrangement is completed, they are twisted together.

[0059] In another example, the outer diameter of a single coarse tin-plated copper wire is 0.52 mm, the outer diameter of the tin-plated copper conductor is 2.60 mm, and the cross-section of the tin-plated copper conductor is 4 mm². 2 The structure of the tin-plated copper conductor is 1 / 0.52+6 / 0.52+12 / 0.52 (strands / mm), and the DC resistance of the tin-plated copper conductor at 20℃ is no greater than 4.74Ω / km.

[0060] In another example, the outer diameter of a single coarse tin-plated copper wire is 0.64 mm, the outer diameter of the tin-plated copper conductor is 3.20 mm, and the cross-section of the tin-plated copper conductor is 6 mm². 2 The structure of the tin-plated copper conductor is 1 / 0.64+6 / 0.64+12 / 0.64 (strands / mm), and the DC resistance of the tin-plated copper conductor at 20℃ is no greater than 3.164Ω / km.

[0061] In another example, the outer diameter of a single coarse tin-plated copper wire is 0.52 mm, the outer diameter of the tin-plated copper conductor is 4.58 mm, and the cross-section of the tin-plated copper conductor is 10 mm². 2The tin-plated copper conductor has a structure of 1 / (7 / 0.52) + 6 / (7 / 0.52) (wires / mm), and its DC resistance at 20℃ is no greater than 1.868Ω / km. In this example, the tin-plated copper conductor is composed of 49 thick tin-plated copper wires with an outer diameter of 0.52mm, twisted together in a regular, layered manner. The arrangement is as follows: first, 7 thick tin-plated copper wires are arranged clockwise in sequence, forming 7 groups. One of these groups is placed in the center. The remaining 6 groups are then arranged clockwise in the second layer, and finally twisted together.

[0062] In another example, the outer diameter of a single coarse tin-plated copper wire is 0.64 mm, the outer diameter of the tin-plated copper conductor is 5.63 mm, and the cross-section of the tin-plated copper conductor is 16 mm². 2 The structure of the tin-plated copper conductor is 1 / (7 / 0.64)+6 / (7 / 0.64) (strands / mm), and the DC resistance of the tin-plated copper conductor at 20℃ is no greater than 1.179Ω / km.

[0063] In another example, the outer diameter of a single coarse tin-plated copper wire is 0.58 mm, the outer diameter of the tin-plated copper conductor is 7.52 mm, and the cross-section of the tin-plated copper conductor is 25 mm². 2 The structure of the tin-plated copper conductor is 4 / (7 / 0.58)+10 / (7 / 0.58) (strands / mm), and the DC resistance of the tin-plated copper conductor at 20℃ is no greater than 0.741Ω / km.

[0064] In another example, the outer diameter of a single coarse tin-plated copper wire is 0.58 mm, the outer diameter of the tin-plated copper conductor is 8.53 mm, and the cross-section of the tin-plated copper conductor is 35 mm². 2 The structure of the tin-plated copper conductor is 1 / (7 / 0.58)+6 / (7 / 0.58)+12 / (7 / 0.58) (strands / mm), and the DC resistance of the tin-plated copper conductor at 20℃ is no greater than 0.534Ω / km.

[0065] To further reduce the cost of the conductor, a second type of aluminum alloy conductor is selected. In one embodiment, the outer diameter of the second type of aluminum alloy conductor is 2.04 mm to 7.47 mm, and the outer diameter of a single wire is 0.68 mm to 2.49 mm.

[0066] In this embodiment, the second type of aluminum alloy conductor is made of multiple aluminum alloy wires twisted together. The twisting method can be regular twisting or bundle twisting. It should also be noted that the performance of the aluminum alloy wire meets the requirements of GB / T 30552-2014 "Aluminum Alloy Wire for Cables"; the structure and resistance of the second type of aluminum alloy conductor meet the requirements of the second type of stranded conductor in GB / T3956-2008 "Conductors of Cables".

[0067] In one example, the outer diameter of a single aluminum alloy wire is 0.68 mm, the outer diameter of the second type of aluminum alloy conductor is 2.04 mm, and the cross-section of the second type of aluminum alloy conductor is 2.5 mm². 2 The second type of aluminum alloy conductor has a structure of 1 / 0.68+6 / 0.68 (strands / mm) and a DC resistance of no more than 12.10Ω / km at 20℃.

[0068] In another example, the outer diameter of a single aluminum alloy wire is 0.85 mm, the outer diameter of the second type of aluminum alloy conductor is 2.55 mm, and the cross-section of the second type of aluminum alloy conductor is 4 mm². 2 The second type of aluminum alloy conductor has a structure of 1 / 0.85+6 / 0.85 (strands / mm) and a DC resistance of no more than 7.85Ω / km at 20℃.

[0069] In another example, the outer diameter of a single aluminum alloy wire is 1.03 mm, the outer diameter of the second type of aluminum alloy conductor is 3.09 mm, and the cross-section of the second type of aluminum alloy conductor is 6 mm². 2 The structure of the second type of aluminum alloy conductor is 1 / 1.03+6 / 1.03 (strands / mm), and the DC resistance of the second type of aluminum alloy conductor at 20℃ is no greater than 5.23Ω / km.

[0070] In another example, the outer diameter of a single aluminum alloy wire is 1.33 mm, the outer diameter of the second-type aluminum alloy conductor is 3.99 mm, and the cross-section of the second-type aluminum alloy conductor is 10 mm². 2 The structure of the second type of aluminum alloy conductor is 1 / 1.33+6 / 1.33 (strands / mm), and the DC resistance of the second type of aluminum alloy conductor at 20℃ is no greater than 3.08Ω / km.

[0071] In another example, the outer diameter of a single aluminum alloy wire is 1.68 mm, the outer diameter of the second-type aluminum alloy conductor is 5.04 mm, and the cross-section of the second-type aluminum alloy conductor is 16 mm². 2 The second type of aluminum alloy conductor has a structure of 1 / 1.68+6 / 1.68 (strands / mm) and a DC resistance of no more than 1.91Ω / km at 20℃.

[0072] In another example, the outer diameter of a single aluminum alloy wire is 2.11 mm, the outer diameter of the second type of aluminum alloy conductor is 6.33 mm, and the cross-section of the second type of aluminum alloy conductor is 25 mm². 2 The structure of the second type of aluminum alloy conductor is 1 / 2.11+6 / 2.11 (strands / mm), and the DC resistance of the second type of aluminum alloy conductor at 20℃ is not greater than 1.20Ω / km.

[0073] In another example, the outer diameter of a single aluminum alloy wire is 2.49 mm, the outer diameter of the second type of aluminum alloy conductor is 7.47 mm, and the cross-section of the second type of aluminum alloy conductor is 35 mm². 2 The structure of the second type of aluminum alloy conductor is 1 / 2.49+6 / 2.49 (strands / mm), and the DC resistance of the second type of aluminum alloy conductor at 20℃ is not greater than 0.868Ω / km.

[0074] To further improve flame retardant performance, in one embodiment, the photovoltaic cable also includes a sheath layer 4. For example... Figure 1 As shown, the sheath layer 4 is located on the outermost side of the photovoltaic cable.

[0075] In one embodiment, the sheath layer comprises 100 parts of polyvinyl chloride resin with a degree of polymerization of 2500, 50-65 parts of plasticizer, 2.5-5.5 parts of UV stabilizer, 10-50 parts of flame retardant, 8-12 parts of heat stabilizer, 15-40 parts of filler, 0.5-2.5 parts of antioxidant, 5-10 parts of processing aid, 1-2 parts of lubricant, and 0.5-2.5 parts of colorant.

[0076] The plasticizer is one or more of trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil, with a mass ratio of (5-10):(3-5):1; the UV stabilizer is two or three of ultra-durable carbon black, rutile titanium dioxide, and benzophenone-12; the flame retardant is a mixture of antimony trioxide, zinc borate, and magnesium hydroxide in a mass ratio of 8:8:10; the heat stabilizer is an organic calcium-zinc composite stabilizer; the filler is activated calcium carbonate; the antioxidant is a mixture of 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane and tris[2,4-di-tert-butylphenyl]phosphite; the processing aid is methacrylate and / or acrylate copolymer; the lubricant is one or more of ethylene bis-stearamide, barium stearate, calcium stearate, and stearic acid; and the colorant is phthalocyanine blue.

[0077] The sheath layer provided in this embodiment is a flame-retardant and UV-resistant sheath layer with a temperature resistance of 125℃. The sheath layer formula is used in conjunction with the insulation layer formula provided in this application. It not only has the advantages of being recyclable and having low production cost, just like the insulation layer material, but also further improves the flame-retardant and heat-resistant properties of the photovoltaic cable, so that the obtained photovoltaic cable meets the requirements of the bundled Class A combustion test, and the carbonization height of the photovoltaic cable in the combustion test is ≤2.5m.

[0078] Therefore, the performance test results of the sheath layer provided in this embodiment are shown in Table 2 below. As can be seen from Table 2, the sheath layer material provided in this embodiment fully meets the various performance indicators of the photovoltaic cable sheath layer. Therefore, the sheath layer material provided in this embodiment can be used as the photovoltaic cable sheath layer.

[0079] Table 2 shows the performance of the sheathing material provided in this embodiment.

[0080]

[0081] In summary, the photovoltaic cable provided in this application includes a conductor 3, an insulation layer 1, a waterproof layer 2, and a sheath layer 4. The performance of the resulting photovoltaic cable is shown in Table 3 below. As can be seen from Table 3, the photovoltaic cable provided in this embodiment fully meets the various performance indicators of photovoltaic cables and can be used in an ambient temperature range of -40℃ to 90℃. In particular, the photovoltaic cable can meet the requirements of Class A burning flame retardant performance in the GB / T19666-2019 standard "General Rules for Flame Retardant and Fire Resistant Wires and Cables or Optical Cables". In its burning test, the carbonization height of the photovoltaic cable is ≤2.5m, which shows that it can achieve the highest level of flame retardant requirements.

[0082] Table 3 Performance of the photovoltaic cable provided in this application

[0083]

[0084] Furthermore, to achieve the above objectives, this application provides a method for preparing a photovoltaic cable, the method comprising steps S100 to S600:

[0085] Step S100: Prepare insulating layer material.

[0086] In one possible implementation, step S100 may include steps S110 to S140:

[0087] Step S110 involves mixing 45%–48% polyvinyl chloride resin with a degree of polymerization of 2500, 20%–24% heat-resistant plasticizer, 5.7%–7% heat stabilizer, 1.13%–1.18% antioxidant, 12%–15.5% flame retardant, 6%–7.5% filler, 2.25%–2.4% processing aid, 0.5%–1.5% lubricant, and 0.02% colorant according to their mass ratios. After complete mixing, the mixture is discharged at 110°C–125°C to obtain a compound. The heat-resistant plasticizer comprises trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil in a mass ratio of 4.50–9.48:11.85–16.28:0–1.90. In one possible embodiment, the mixing equipment can be a high-speed mixer.

[0088] Step S120: The mixture is extruded and plasticized at an extrusion temperature of 120°C to 180°C; in one possible embodiment, the extrusion and plasticizing equipment can be a twin-screw extruder.

[0089] Step S130: The extruded mixture is extruded and hot-cut air-cooled granulated at an extrusion temperature of 150°C to 180°C to obtain granules; in one possible embodiment, the equipment for hot-cut air-cooled granulation can be a single-screw extruder.

[0090] In step S140, the extruded granules are dried and cooled to obtain an insulating layer material.

[0091] Step S200: Prepare the sheath layer material.

[0092] In one possible implementation, step S200 may include steps S210 to S240:

[0093] In step S210, 100 parts of polyvinyl chloride resin with a degree of polymerization of 2500, 50-65 parts of plasticizer, 2.5-5.5 parts of UV stabilizer, 10-50 parts of flame retardant, 8-12 parts of heat stabilizer, 15-40 parts of filler, 0.5-2.5 parts of antioxidant, 5-10 parts of processing aid, 1-2 parts of lubricant, and 0.5-2.5 parts of colorant are mixed according to the mass proportions. After complete mixing, the mixture is discharged at 110°C-125°C to obtain a mixture. In one possible embodiment, the mixing equipment can be a high-speed mixer.

[0094] Step S220: The mixture is extruded and plasticized at an extrusion temperature of 120°C to 180°C; in one possible embodiment, the extrusion and plasticizing equipment may be a twin-screw extruder.

[0095] Step S230: The extruded mixture is extruded and hot-cut air-cooled granulated at an extrusion temperature of 150°C to 180°C to obtain granules; in one possible embodiment, the equipment for hot-cut air-cooled granulation can be a single-screw extruder.

[0096] In step S240, the extruded granules are dried and cooled to obtain the sheath layer material.

[0097] Step S300: Prepare the conductor.

[0098] In one possible implementation, step S300 may include steps S310 to S320:

[0099] Step S310 involves drawing the copper rod and annealing it before tin plating to obtain coarse tin-plated copper wire; in one possible implementation, the drawing process includes large-scale drawing and multi-head drawing.

[0100] In step S320, the multiple coarse tin-plated copper wires obtained are twisted together in a regular arrangement and in layers to form a tin-plated copper conductor. It should also be noted that the surface of the obtained conductor should be bright and round, free from manufacturing defects such as skipped wires, broken wires, wire lugs, incomplete plating, oxidation, oil stains, inclusions, and burrs.

[0101] In another possible implementation, step S300 may include steps S311 to S321:

[0102] Step S311: After the aluminum alloy rod is drawn, an aluminum alloy wire is obtained; in one possible implementation, the drawing includes large drawing and medium drawing.

[0103] In step S321, after the multiple aluminum alloy wires are twisted together, they undergo high-temperature aging treatment and pass inspection to obtain a second type of aluminum alloy conductor. It should also be noted that the surface of the obtained second type of aluminum alloy conductor should be smooth and free from defects such as wavy lines, oil stains, burrs, sharp edges, mechanical damage, protrusions, and broken wires.

[0104] Step S400: Extruding insulating material onto the surface of the conductor to form an insulating layer, thereby obtaining an insulated wire core; in one possible embodiment, the extrusion equipment may be an extruder.

[0105] In step S500, after passing the spark test, an aluminum-plastic or steel-plastic composite waterproof layer is longitudinally wrapped around the surface of the insulated wire core, while extruding a sheath layer material to form a sheath layer; in one possible embodiment, the equipment for longitudinal wrapping and extrusion can be an extruder.

[0106] In step S600, after the finished product passes inspection, it is packaged and stored. The specific structural dimensions and insulation resistance parameters of the photovoltaic cable are shown in Tables 4 and 5 below. The current carrying capacity parameters of the photovoltaic cable when the ambient temperature is 60℃ and the conductor temperature is 120℃ are shown in Table 6 below.

[0107] Table 4. Structural Dimensions and Insulation Resistance Parameters of Photovoltaic Cables (Tin-plated Copper Conductors)

[0108]

[0109] Table 5. Structural Dimensions and Insulation Resistance Parameters of Photovoltaic Cables (Class II Aluminum Alloy Conductors)

[0110]

[0111] Table 6. Photovoltaic Cable Current Carrying Capacity Parameters

[0112]

[0113] The preparation method of this photovoltaic cable is based on the above embodiments. Since the preparation method of this photovoltaic cable adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.

[0114] The technical features of the technical solution provided in this application will be described more clearly and completely below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application. Where specific technologies or conditions are not specified in the embodiments, they shall be performed in accordance with the technologies or conditions described in the literature in the art or in accordance with the product instructions. Reagents or instruments used without specified manufacturers are all conventional products that can be obtained commercially.

[0115] Example 1

[0116] The insulation layer comprises the following components by weight percentage: 47.38% polyvinyl chloride resin with a degree of polymerization of 2500, heat-resistant plasticizer (9.48% trioctyl trimellitate TOTM, 11.85% tridecyl trimellitate TNTM and 1.90% epoxidized soybean oil), 5.69% organic calcium-zinc composite environmentally friendly stabilizer, 1.18% antioxidant 1010, flame retardant (3.79% antimony trioxide, 3.79% zinc aluminate and 4.74% secondary flame retardant; wherein the secondary flame retardant is aluminum hydroxide and magnesium hydroxide in a mass ratio of 2:1), 7.11% combustible kaolin, 2.37% ACR (acrylate copolymer), 0.71% light barium stearate and 0.02% lithol red.

[0117] Example 2

[0118] The insulation layer comprises the following components by weight percentage: 46.72% polyvinyl chloride resin with a degree of polymerization of 2500, 7.01% trioctyl trimellitate TOTM, 14.02% tridecyl trimellitate TNTM, 1.87% epoxidized soybean oil, 6.07% organic calcium-zinc composite environmentally friendly stabilizer, 1.17% antioxidant 1010, 2.80% antimony trioxide, 2.80% zinc borate, 7.01% magnesium hydroxide and aluminum hydroxide (wherein the mass ratio of aluminum hydroxide to magnesium hydroxide is 2:1), 7.01% combustible kaolin, 2.34% ACR (acrylate copolymer), 1.17% light barium stearate, and 0.02% Lithol Rubber Red.

[0119] Example 3

[0120] The insulation layer comprises the following components by weight percentage: 45.03% polyvinyl chloride resin with a degree of polymerization of 2500, 4.50% trioctyl trimellitate (TOTM), 15.76% tridecyl trimellitate (TNTM), 1.80% epoxidized soybean oil, 6.30% organic calcium-zinc composite environmentally friendly stabilizer, 1.13% antioxidant 1010, 3.15% antimony trioxide, 3.15% zinc aluminate, 9.01% magnesium hydroxide and aluminum hydroxide (wherein the mass ratio of aluminum hydroxide to magnesium hydroxide is 2:1), 6.76% combustible kaolin, 2.25% ACR (acrylate copolymer), 1.13% light barium stearate, and 0.02% lithol red.

[0121] Example 4

[0122] The insulation layer comprises the following components by weight percentage: 46.50% polyvinyl chloride resin with a degree of polymerization of 2500, 4.65% trioctyl trimellitate TOTM, 16.28% tridecyl trimellitate TNTM, 6.98% organic calcium-zinc composite environmentally friendly stabilizer, 1.16% antioxidant 1010, 2.33% antimony trioxide, 2.33% zinc borate, 9.30% magnesium hydroxide and aluminum hydroxide (wherein the mass ratio of aluminum hydroxide to magnesium hydroxide is 2:1), 6.98% combustible kaolin, 2.33% ACR (acrylate copolymer), 1.16% light barium stearate, and 0.02% lithol red.

[0123] The flame-retardant PVC insulation materials with a temperature resistance of 125℃ prepared in Examples 1 to 4 were subjected to performance tests, and the test results are shown in Table 7. As can be seen from Table 7, the oxygen index of the insulation material in Example 1 reached 33, the oxygen index of Example 2 was 31.5, and the oxygen index of Example 3 was 32.5. Therefore, the flame-retardant performance of Example 1 is better than that of Examples 2 and 3. Furthermore, since zinc aluminate was used in Examples 1 and 3, the cost was slightly increased. Therefore, based on cost and performance considerations, Example 4 is preferred.

[0124] Table 7 Test Results of Insulation Layer Material Performance

[0125]

[0126] Comparative Example 1

[0127] The only difference between this comparative example and Example 1 is that the plasticizer is 23.23% dioctyl phthalate (DOP).

[0128] The insulating material prepared in Comparative Example 1 was subjected to performance tests. The heat distortion at 135℃ was >20, the tensile strength after heat aging at 158℃ was ≤18.5, and the elongation at break after heat aging at 158℃ was less than 150%. It is evident that all three properties fail to meet the technical requirements. Therefore, replacing the plasticizer provided in this application with a more conventional plasticizer will decrease the temperature resistance of the resulting insulating material.

[0129] The above description is only a part of the embodiments of this application and does not limit the scope of protection of this application. All equivalent structural transformations made under the technical concept of this application and using the contents of the specification and drawings of this application, or direct / indirect applications in other related technical fields, are included in the patent protection scope of this application.

Claims

1. A photovoltaic cable, characterized in that, The photovoltaic cable includes an insulation layer; The insulating layer comprises the following components by weight percentage: 45%–48% polyvinyl chloride resin with a degree of polymerization of 2500, 20%–24% heat-resistant plasticizer, 5.7%–7% heat stabilizer, 1.13%–1.18% antioxidant, 12%–15.5% flame retardant, 6%–7.5% filler, 2.25%–2.4% processing aid, 0.5%–1.5% lubricant, and 0.02% colorant; The heat-resistant plasticizer includes trioctyl trimellitate, tridecyl trimellitate, and epoxidized soybean oil; or, the heat-resistant plasticizer includes trioctyl trimellitate and tridecyl trimellitate.

2. The photovoltaic cable as described in claim 1, characterized in that, The mass ratio of the trioctyl trimellitate, the tridecyl trimellitate, and the epoxidized soybean oil is (4.50–9.48):(11.85–16.28):(0–1.90).

3. The photovoltaic cable as described in claim 1, characterized in that, The flame retardant comprises a primary flame retardant, a secondary flame retardant, and a synergist in a mass ratio of (2.33–3.79):(2.33–3.79):(4.74–9.30); The primary flame retardant is antimony trioxide, the secondary flame retardant is aluminum hydroxide and magnesium hydroxide in a mass ratio of 2:1, and the synergist is zinc borate or zinc aluminate.

4. The photovoltaic cable as described in claim 1, characterized in that, The heat stabilizer is an organic calcium-zinc composite environmentally friendly stabilizer, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], the filler is combustible kaolin, the processing aid is an acrylate copolymer, the lubricant is light barium stearate, and the colorant is Lisol Bronze Red.

5. The photovoltaic cable as described in claim 1, characterized in that, The polyvinyl chloride resin with a degree of polymerization of 2500 accounts for 46.50% by mass, the trioctyl trimellitate accounts for 4.65% by mass, the tridecyl trimellitate accounts for 16.28% by mass, the heat stabilizer accounts for 6.98% by mass, the antioxidant accounts for 1.16% by mass, the flame retardant accounts for 13.93% by mass, the filler accounts for 6.98% by mass, the processing aid accounts for 2.23% by mass, the lubricant accounts for 1.16% by mass, and the colorant accounts for 0.02% by mass.

6. The photovoltaic cable as described in any one of claims 1-5, characterized in that, The photovoltaic cable also includes a waterproof layer, which is disposed on the outside of the insulation layer; The waterproof layer is made of steel-plastic composite tape tightly wrapped longitudinally. The steel-plastic composite tape includes a steel layer and a plastic layer. The steel layer is disposed outside the insulation layer, and the plastic layer is disposed outside the steel layer.

7. The photovoltaic cable as described in any one of claims 1-6, characterized in that, The photovoltaic cable also includes a conductor, which is disposed inside the insulation layer, and the conductor is a tin-plated copper conductor or a type II aluminum alloy conductor.

8. The photovoltaic cable as described in claim 7, characterized in that, The tin-plated copper conductor is formed by twisting together multiple coarse tin-plated copper wires in a regular arrangement and in layers. The outer diameter of the coarse tin-plated copper wires is 0.4mm to 0.64mm, and the outer diameter of the tin-plated copper conductor is 2.00mm to 8.53mm.

9. The photovoltaic cable as described in claim 7, characterized in that, The outer diameter of the second type of aluminum alloy conductor is 2.04mm to 7.47mm, and the diameter of a single wire is 0.68mm to 2.49mm.

10. The photovoltaic cable according to any one of claims 1-9, characterized in that, The photovoltaic cable also includes a sheath layer, which is disposed on the outermost side of the photovoltaic cable.